GAMBARAN MEKANISME KOPING WANITA DALAM MENGHADAPI PERUBAHAN FISIK AKIBAT MENOPAUSE - Tsuraya, Mona; Zulfitri, Reni; Arneliwati, Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Menopause is one of the reproductive cycles that will be run by every woman. The existence of these physical changes causes some problems in woman so it needed the adaptive coping mechanism in dealing with it. This study aims to determine the description of woman coping mechanisms to confront the physical changes due to menopause in the work area of Payung Sekaki Pekanbaru Health Center. Design research used is descriptive design research. The sample are 92 respondents taken based on the inclusion criteria using purposive sampling technique. Measuring devices used are the questionare of respondent characteristic and questionare of coping mechanism that valid and reliable. The analysis used the univariate analysis to know the distribution of respondent characteristic and the coping mechanism used. The results of study showed the most respondents ages are 50-55 years old, 42 people (45.7%), 30 people had first menstruation at the age of 14 years (32.6%), 13 people had the last menstrual period at the age of 48 years (14,1%), the majority married respondents were 84 people (91.3%), 28 people had 3 children (30.4%), 53 were high school graduates (57.6%), 49 were housewives (53.3%) and the most family income is 1-2 million amounted to 37 people (40.2%). For 92 respondents there were 59 respondents using an adaptive coping mechanism (64,1%), while 33 respondents using maladaptive coping mechanism (35,9%). Suggested to premenopause woman to find the information about menopause that they can use adaptive coping mechanism.Keywords: Coping mechanism, menopause, physical changes